Talent identification and talent development programmes - with particular regard to soccer - Güllich, A. (International Symposium for MEXT Top Global Project, March 6, 2016, 2016)
Q1 Future `top athletes` cannot be predicted reliably by way of TID at a young age. Q2 Particularly early TDP involvement is neither necessary nor beneficial, but correlates negatively with long-term senior success. Q3 Early TID and TDP preferentially selects, and further reinforces, developmental participation patterns that are inconsistent with those patterns likely leading to long-term international senior success. Q4 The population of senior top athletes emerges in the course of repeated selection, de-selection, and replacement across all age ranges; rather than originating from early selected youngsters and their continuous TDP nurturing.